Secukinumab in moderate-to-severe plaque psoriasis: a multi-center, retrospective, real-life study up to 52 weeks observation. (3rd July 2018) - Galluzzo, Marco; Talamonti, Marina; De Simone, Clara; D'Adamio, Simone; Moretta, Gaia; Tambone, Sara; Caldarola, Giacomo; Fargnoli, Maria Concetta; Peris, Ketty; Bianchi, Luca
ABSTRACT: Objectives : To evaluate efficacy and safety of the anti-IL-17 drug secukinumab in a real-life large cohort of patients with moderate-to-severe plaque psoriasis in Central Italy. Methods : Multicenter, retrospective study with an observation period of up to 52 weeks. Efficacy was assessed by Psoriasis Area and Severity Index (PASI) score; clinical and laboratory examinations were performed at baseline and at weeks 4, 12, 24, 36, and 52. Results : A 90% and a 100% PASI score reduction (PASI90 and PASI100) were reported in 67.5% and 55% of patients at week 12, respectively. A rapid improvement of skin lesions was observed particularly in young patients and in patients naïve to biologics: at week 4, the achievement of PASI90 and PASI100 was higher in younger patients (odds ratio [OR] 0.95, and 0.95; p = 0.003, and 0.005, respectively); PASI90 was achieved by 42.0% of patients naïve to biologics and by 17.0% of patients with prior exposure to biologics (PBT) (OR 0.24; p = 0.001); and PASI100 was reached by 25.5% of naïve patients and 9.8% of PBT (OR 0.28; p = 0.015).The drug was well tolerated. Conclusion : Secukinumab was effective in this real-life analysis, with rapid clinical improvement and long-term maintenance of results.